Borderline, avoidant, sadistic personality traits and emotion dysregulation predict different pathological skin picking subtypes in a community sample - Pozza A; Giaquinta N; Dèttore D (Neuropsychiatric Disease and Treatment, 2016)
Andrea Pozza,1,2 Nicoletta Giaquinta,2,3 Davide Dèttore4 1Department of Experimental and Clinical Medicine, University of Florence, Florence, 2Miller Institute of Behavioral and Cognitive Psychotherapy, Genoa, 3Centre of Cognitive and Behavioural Therapy (CTCC), Florence, 4Department of Health Sciences, University of Florence, Florence, Italy Abstract: Pathological skin picking (SP) is a strongly impairing condition characterized by repetitive picking behaviors resulting in significant tissue damage and distress. Recent research suggested the presence of different subtypes of SP. No study has investigated which personality traits could be specifically associated with different subtypes. In a community sample (N=285, 71.20% females, mean age =34.98 years, standard deviation =15.91), this cross-sectional study investigated which personality traits and emotion regulation deficits could predict specific SP subtypes. Participants completed the Milwaukee Inventory for the Dimensions of Adult Skin Picking (MIDAS), Millon Clinical Multiaxial Inventory-III personality scales (MCMI-III), and Difficulties in Emotion Regulation Scale (DERS) questionnaires. Higher scores on the MCMI-III borderline (β=0.28, t=4.88, P<0.001), MCMI-III avoidant scale (β=0.18, t=2.59, P<0.01), and DERS difficulties engaging in goal-directed behavior (β=0.19, t=3.27, P<0.01) predicted higher scores on the MIDAS automatic scale. Higher scores on the MCMI-III borderline (β=0.30, t=5.23, P<0.001) and DERS difficulties engaging in goal-directed behavior (β=0.15, t=2.52, P<0.05) and DERS limited access to emotion regulation strategies (β=0.21, t=3.26, P<0.01) predicted higher scores on the MIDAS focused scale. Higher scores on the MCMI-III sadistic (β=0.19, t=3.30, P<0.001) and DERS difficulties engaging in goal-directed behavior (β=0.15, t=2.68, P<0.01) predicted higher scores on the MIDAS mixed scale. Implications for future research and treatment are discussed. Keywords: skin picking, personality traits, emotion dysregulation, subtypes, MIDAS